2018
DOI: 10.3390/su10051644
|View full text |Cite
|
Sign up to set email alerts
|

Women on Boards and Financial Performance: Evidence from a European Emerging Market

Abstract: This paper examines the association between gender diversity on corporate boards and firm performance for a European emerging market, which lags behind in terms of both corporate governance quality and social cohesion indicators. In a sample of Romanian companies listed on BSE (Bucharest Stock Exchange) during 2012-2016, this study confirms previous concerns related to the endogeneity of gender diversity variables in firm performance regression analysis and shows that, on average, diversity has no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 35 publications
4
56
0
16
Order By: Relevance
“…Accordingly, no correlation between the percentage of women on boards and the financial performance criteria was determined. These results are consistent with some studies in the literature [12,16,18,20,45,57,58]. Brindelli et al [15] diversely showed that the relationship between women on boards and a bank's ESG performance is an inverted U-shape.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Accordingly, no correlation between the percentage of women on boards and the financial performance criteria was determined. These results are consistent with some studies in the literature [12,16,18,20,45,57,58]. Brindelli et al [15] diversely showed that the relationship between women on boards and a bank's ESG performance is an inverted U-shape.…”
Section: Discussionsupporting
confidence: 90%
“…Sustainable social participation policies such as compulsory gender quotas on boards ensure financial sustainability and produce positive economic outputs for shareholders [20]. The original value and contribution of this study is its demonstration that women are being appointed to boards without being ready, just to fill compulsory or voluntary female member quotas.…”
Section: Conclusion Recommendations and Limitationsmentioning
confidence: 94%
See 2 more Smart Citations
“…For those reasons, there are many papers linking only one dimension of corporate governance practices and CFP. For example, Post & Byron [53] and Ionascu et al [54] focused on one dimension of good governance practices (i.e., board gender composition) on CFP. Based on firms' board independence, Rhoades et al [14] analyzed its influence on CFP.…”
Section: Linking Board Independence and Corporate Financial Performancementioning
confidence: 99%